Increasing Explicit Sequence Knowledge by Odor Cueing during Sleep in Men but not Women - Diekelmann, Susanne (Front Behav Neurosci, 2016)
Sleep consolidates newly acquired memories. Beyond stabilizing memories, sleep is thought to reorganize memory representations such that invariant structures, statistical regularities and even new explicit knowledge are extracted. Whereas increasing evidence suggests that the stabilization of memories during sleep can be facilitated by cueing with learning-associated stimuli, the effect of cueing on memory reorganization is less well understood. Here we asked whether olfactory cueing during sleep enhances the generation of explicit knowledge about an implicitly learned procedural memory task. Subjects were trained on a serial reaction time task (SRTT) containing a hidden 12-element sequence in the presence of an odor. During subsequent sleep, half of the subjects were re-exposed to the odor during periods of slow wave sleep (SWS), while the other half received odorless vehicle. In the next morning, subjects were tested on their explicit knowledge about the underlying sequence in a free recall test and a generation task. Although odor cueing did not significantly affect overall explicit knowledge, differential effects were evident when analyzing male and female subjects separately. Explicit sequence knowledge, both in free recall and the generation task, was enhanced by odor cueing in men, whereas women showed no cueing effect. Procedural skill in the SRTT was not affected by cueing, neither in men nor in women. These findings suggest that olfactory memory reactivation can increase explicit knowledge about implicitly learned information, but only in men. Hormonal differences due to menstrual cycle phase and/or hormonal contraceptives might explain the lacking effect in women.